Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran IPAS Materi Fotosintesis, Proses Penting di Bumi pada Kelas IV UPTD SD Inpres Oesapa Kecil 1 - Kote, Esma; Koten, Angelikus N.; Ratu, Kurniayu Triastuti R.A. (Lembaga Yasin AlSys, 2025)
This study is motivated by the low student achievement in the topic of photosynthesis, a vital life process, at UPTD SD Inpres Oesapa Kecil 1. The aim of the research is to improve student learning outcomes through the implementation of the problem based learning (PBL) model. This classroom action research (CAR) was conducted in two cycles, involving 29 students as research subjects. Data collection techniques included observation, interviews, documentation, and learning outcome tests. The results showed that the application of the PBL model significantly improved student learning outcomes, with the average score increasing from 67.28 in the first cycle to 81.65 in the second cycle, and learning mastery rising from 62.07 percent to 93.10 percent. The conclusion of this study is that the PBL model is effective in enhancing students’ understanding of the photosynthesis concept through active and contextual learning. The implications of these findings emphasize the importance of applying problem based learning approaches to improve the quality of science and social studies education (IPAS) at the elementary school level and highlight the need for teacher training to consistently implement innovative teaching models.